Paediatric prescribing error – moving towards zero tolerance. (24th May 2012) - Woodley, N; Teh, A; Hewitt, I; Alexander, V; Clerihew, L
Abstract : Aim: To reduce the inpatient prescription error rate to <100 errors /1000 drugs prescribed, in our department, by 31st January 2012. Background: Drug errors, both prescribing and administration, are the commonest cause for adverse event reports and complaints within our department. Reducing this error rate is one of our top priorities within our paediatric patient safety programme. Methods: A set of 18 recommended standards for safe paediatric prescribing was created by our paediatric pharmacy team. During intervention periods the prescription chart of all patients admitted in the preceding 24 hours is compared to these standards and scored as 'compliant' or 'error' for each drug prescribed. Applying improvement methodology, the baseline error rate was calculated and interventions conducted via Plan-Do-Study-Act (PDSA) cycles. Tests of change included verbally informing and emailing staff of the most common errors, publication of error rate on the patient safety noticeboard visible to staff and the public, and reward schemes for highly performing staff. As the error rate failed to decline, individual prescribers' data was published in the doctor's room and forwarded to educational supervisors. Results: Our baseline prescribing error rate using these stringent 18 criterion was 909 errors /1000 drugs prescribed in May 2010. There has been a downward trend with an error rate of 242 errors/1000 drugs prescribed in October 2010, however run chart rules demonstrating significant improvement are yet to be met. Run charts for the 5 most common errors demonstrate improvement in some, but not all criterion, and others demonstrate initial improvement which is not sustained. The most significant improvement has been seen following the publication of individual prescriber's data (figure 1 ). Conclusion: The reasons for poor prescribing practice are complex and whilst we are encouraged by initial improvements we still have a journey to reach our aim. This project is ongoing and new PDSA ideas are welcomed. We are currently adapting our induction programme and researching paediatric prescribing e-resources and exams. We believe other centres starting this journey could learn from our experience.